2020
DOI: 10.3390/antiox9111050
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Green Tea on Joint and Skeletal Muscle Health: Prospects of Translational Nutrition

Abstract: Osteoarthritis and sarcopenia are two major joint and skeletal muscle diseases prevalent during aging. Osteoarthritis is a multifactorial progressive degenerative and inflammatory disorder of articular cartilage. Cartilage protection and pain management are the two most important strategies in the management of osteoarthritis. Sarcopenia, a condition of loss of muscle mass and strength, is associated with impaired neuromuscular innervation, the transition of skeletal muscle fiber type, and reduced muscle regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 164 publications
0
29
0
1
Order By: Relevance
“…The bone healthy effects of antioxidant have also been shown in human studies [ 15 , 16 ]. Green tea catechins are potent antioxidants that have been extensively studied for their joint and muscle protective effects [ 36 ]. In this review, we examine the effects of green catechins on bone in the literature.…”
Section: Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…The bone healthy effects of antioxidant have also been shown in human studies [ 15 , 16 ]. Green tea catechins are potent antioxidants that have been extensively studied for their joint and muscle protective effects [ 36 ]. In this review, we examine the effects of green catechins on bone in the literature.…”
Section: Osteoporosismentioning
confidence: 99%
“…EGCG possesses the most potent antioxidant and free radical scavenging abilities [ 39 , 40 ]. Thus, many benefits of green tea come from the free radical scavenging activity and antioxidant effects of catechins [ 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Catechinsmentioning
confidence: 99%
“…However, there is currently no effective pharmaceutical therapies to attenuate the course of OA progression [ 64 ]. EGCG is considered as a potential therapeutic agent for OA because of its potent anti-inflammatory and antioxidative properties [ 30 ]. Besides previous health effects, in this study, we further found that the levels of p16 Ink4a gene expression and SAβGal activity were markedly decreased in IL-1β-stimulated HAC after EGCG treatment, indicating EGCG may attenuate chondrocyte cell senescence after IL-1β stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…(−)-Epigallocatechin 3-gallate (EGCG), the major bioactive component of green tea catechins, has gained interest in OA research because of its potent anti-inflammatory and antioxidative properties [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The chondroprotective effect of EGCG has been widely investigated using human articular chondrocytes [ 22 , 23 , 24 ], animal articular chondrocytes [ 25 , 26 ], bovine cartilage explants [ 27 ], and surgically induced OA animal models [ 28 , 29 , 30 ]. These studies have demonstrated that EGCG could mitigate OA progression by inhibiting the expression of proinflammatory genes (i.e., cyclooxygenase 2 (COX-2), matrix metalloproteinase-1(MMP-1), MMP-3, MMP-13, inducible nitric oxide synthase, tumor necrosis factor-α (TNF-α), transforming growth factor-β2, a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-5, aggrecanase-1, -2) [ 22 , 23 , 26 , 28 , 31 , 32 , 33 ], reducing the production of nitric oxide [ 22 , 34 ] and prostaglandin E2 [ 32 , 35 ], as well as increasing chondrogenic regeneration genes (i.e., aggrecan, collagen type II (Col II), and SOX9) [ 25 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…(-)-Epigallocatechin 3-gallate (EGCG), the most plentiful bioactive polyphenol of green tea, is a potential anti-arthritic agent because of its anti-inflammatory effect and anti-oxidant effect [ 11 , 12 ]. Studies have shown that EGCG inhibits nitric oxide, cyclooxygenase-2 (COX-2), and the production of prostaglandin E2 in human OA chondrocytes stimulated with interleukin-1β (IL-1β) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%